MHC and Evolution in Teleosts - Unni Grimholt (Biology, 2016)
Major histocompatibility complex (MHC) molecules are key players in initiating immune responses towards invading pathogens. Both MHC class I and class II genes are present in teleosts, and, using phylogenetic clustering, sequences from both classes have been classified into various lineages. The polymorphic and classical MHC class I and class II gene sequences belong to the U and A lineages, respectively. The remaining class I and class II lineages contain nonclassical gene sequences that, despite their non-orthologous nature, may still hold functions similar to their mammalian nonclassical counterparts. However, the fact that several of these nonclassical lineages are only present in some teleost species is puzzling and questions their functional importance. The number of genes within each lineage greatly varies between teleost species. At least some gene expansions seem reasonable, such as the huge MHC class I expansion in Atlantic cod that most likely compensates for the lack of MHC class II and CD4. The evolutionary trigger for similar MHC class I expansions in tilapia, for example, which has a functional MHC class II, is not so apparent. Future studies will provide us with a more detailed understanding in particular of nonclassical MHC gene functions.